2015
DOI: 10.1038/npp.2015.69
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine Administration Exacerbates Oral Tremor and Striatal Dopamine Depletion in a Rodent Pharmacological Model of Parkinsonism

Abstract: The cardinal motor symptoms of Parkinson's disease (PD) include resting tremor, akinesia, bradykinesia, and rigidity, and these motor abnormalities can be modeled in rodents by administration of the VMAT-2 (type-2 vesicular monoamine transporter) inhibitor tetrabenazine (9,10-dimethoxy-3-(2-methylpropyl)-1,3,4,6,7, 11b hexahydrobenzo[a]quinolizin-2-one; TBZ). Depression is also commonly associated with PD, and clinical data indicate that selective serotonin reuptake inhibitors (SSRIs) such as fluoxetine ((±)-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…These results obtained from animal studies are consistent with clinical data showing a reduced selection of high effort alternatives in depressed people tested on tasks of effort-based choice (Treadway et al, 2012;Chong et al, 2016). Administration of the vesicular monoamine transporter (VMAT-2) inhibitor tetrabenazine (TBZ), which blocks the monoamine storage and leads to a striatal DA depletion at low doses in primates (Pettibone et al, 1984), rats (Nunes et al, 2013;Podurgiel et al, 2015Podurgiel et al, , 2016Yohn et al, 2015b), and mice (López-Cruz et al, 2018;Carratalá-Ros et al, 2020) has been used to induce effort-related motivational impairments in rodents (Nunes et al, 2014;Yohn et al, 2015bYohn et al, , 2016bCorrea et al, 2018;López-Cruz et al, 2018;Rotolo et al, 2019;Carratalá-Ros et al, 2020). This drug is used in the treatment of Huntington's disease and has been reported to produce depressive symptoms including fatigue in people (Frank, 2009;Guay, 2010).…”
Section: Introductionsupporting
confidence: 76%
“…These results obtained from animal studies are consistent with clinical data showing a reduced selection of high effort alternatives in depressed people tested on tasks of effort-based choice (Treadway et al, 2012;Chong et al, 2016). Administration of the vesicular monoamine transporter (VMAT-2) inhibitor tetrabenazine (TBZ), which blocks the monoamine storage and leads to a striatal DA depletion at low doses in primates (Pettibone et al, 1984), rats (Nunes et al, 2013;Podurgiel et al, 2015Podurgiel et al, , 2016Yohn et al, 2015b), and mice (López-Cruz et al, 2018;Carratalá-Ros et al, 2020) has been used to induce effort-related motivational impairments in rodents (Nunes et al, 2014;Yohn et al, 2015bYohn et al, , 2016bCorrea et al, 2018;López-Cruz et al, 2018;Rotolo et al, 2019;Carratalá-Ros et al, 2020). This drug is used in the treatment of Huntington's disease and has been reported to produce depressive symptoms including fatigue in people (Frank, 2009;Guay, 2010).…”
Section: Introductionsupporting
confidence: 76%
“…But two duloxetine-treated PD patients showed an exacerbation of tremor in a multicenter randomized study (33), which however was not seen in another study of patients treated with duloxetine (34). Moreover, an animal study showed that administration of fluoxetine exacerbated oral tremor (35). Similar to 5-HTTLPR, rs25531 is also a functional polymorphism with the G allele leading to reduced efficiency of HTT transcription (9).…”
Section: Discussionmentioning
confidence: 99%
“…To my knowledge, there is no convincing empirical evidence that shows the efficacy of serotonergic medication for treating resting tremor. On the contrary, in parkinsonian rodents, serotonin reuptake inhibitors worsen tremor by further depleting dopamine . Furthermore, postmortem studies have not found different patterns or degrees of serotonergic cell death between tremor‐dominant and nontremor PD patients .…”
Section: Is Parkinsonian Tremor Related To Dopamine Depletion?mentioning
confidence: 99%